2000
DOI: 10.1046/j.1365-2222.2000.00820.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative structural and biochemical analyses of tight junction dynamics following exposure of epithelial cells to house dust mite allergen Der p 1

Abstract: Der p 1 could contribute to sensitization and allergic responses by degrading the function of the airway epithelial barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
137
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(144 citation statements)
references
References 36 publications
4
137
1
1
Order By: Relevance
“…These events have been poorly studied to date and they may be of great importance in the development of the allergic inflammation and our understanding of asthma pathology. It is currently believed that when HDM allergens interact with the bronchial epithelium, they induce direct damage through protease activity, disrupting the epithelial tight junctions and thereby increasing the bronchial epithelium permeability and facilitating trans-epithelial allergen delivery and interaction with antigen presenting cells [5][6][7]. We have demonstrated that HDM allergens can interact with the lung, particularly the airway epithelium, and induce asthma-like inflammation, i.e.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These events have been poorly studied to date and they may be of great importance in the development of the allergic inflammation and our understanding of asthma pathology. It is currently believed that when HDM allergens interact with the bronchial epithelium, they induce direct damage through protease activity, disrupting the epithelial tight junctions and thereby increasing the bronchial epithelium permeability and facilitating trans-epithelial allergen delivery and interaction with antigen presenting cells [5][6][7]. We have demonstrated that HDM allergens can interact with the lung, particularly the airway epithelium, and induce asthma-like inflammation, i.e.…”
Section: Discussionmentioning
confidence: 89%
“…Der p 1 belongs to the papain-like cysteine protease family and exhibits cysteine protease activity [4]. This proteolytic activity has been suggested to be involved in the pathogenesis of allergies by: increasing the permeability of epithelial cells and allowing the passage of their own and other allergens across the epithelium [5][6][7]; cleaving and/or interacting with cell surface molecules and intrinsic protease inhibitors [8][9][10][11]; and modulating the function of a range of cells, such as basophils, mast cells, alveolar macrophages and airway epithelial cells [12][13][14][15]. The effect on the airway epithelium is especially interesting, as it is likely to be the first cell type to interact with the allergen.…”
mentioning
confidence: 99%
“…Alternatively, neutrophil recruitment to the airways could be mediated directly by HDM allergen. HDMs produce enzymes called proteases that cleave peptide bonds of tight junction in the epithelial cell layer (57)(58)(59), and this action occurs by the binding of proteases to protease activator receptors that are found on airway epithelial cells (60). The binding of proteases causes the production and secretion of IL-6 and -8 (61).…”
Section: Discussionmentioning
confidence: 99%
“…In other respects, some of the data previously reported for the action of Der p 1 via PAR 2 (14) appear somewhat contradictory. In one study by those investigators (12), it was shown that Der p 1 and Der p 9 induce the release of GM-CSF, IL-6, and IL-8 in bronchial epithelial cells. However, it was suggested in that study that these two mite allergens act presumably via different receptors (potentially PARs), since the calcium response generated in the BEAS-2B target cells by Der p 1 treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%